Melanin nanoparticles as a novel contrast agent for optoacoustic tomography - Liopo, Anton (Photoacoustics, 2015)
We describe the synthesis and characterization of melanin-like nanoparticles (MNP) as novel contrast agents for optoacoustic tomography. Good dispersion stability of high concentration MNPs in different biological media was achieved with thiol-terminated methoxy-poly(ethylene glycol), which can be used for further functional conjugation. MNP-PEG were found biocompatible with human MCF-7 and 3T3 cells. Cell toxicity of MNPs was found lower than that of gold nanorods for concentrations that provide equal optical absorbance. Optoacoustic tomography images were obtained with Laser Optoacoustic Imaging System (LOIS-3D) from tubes filled with contrast agents and live mice. Imaging of tubes permitted verification of the system resolution <300 μm and sensitivity Δμa=0.03/cm under safe laser fluence of 20 mJ/cm(2). Water suspensions of MNP demonstrated optoacoustic efficiency that is about equal to that of gold nanorods under conditions of equal optical absorption. We conclude that MNPs have the potential for biomedical imaging applications as optoacoustic contrast agents.